Bahan Ajar PJOK Tematik Terpadu Berbasis Permainan Sederhana di Sekolah Dasar - Hari Santoso; Harwanto Harwanto; Hari Karyono (Universitas Mathla'ul Anwar Banten, 2021)
The purpose of this development research is to: (1) explain the validity of the use of Integrated Thematic PJOK teaching materials based on simple games on Theme 1 Rukun Life class II Elementary School SDN Rungkut Menanggal I / 582 Surabaya, (2) produce integrated thematic PJOK teaching materials based on a simple game developed on the theme of 1 harmonious life in class II Elementary Schools, (3) resulting in an Integrated Thematic PJOK learning video based on simple games (VCD). This study uses a Research and Development research methodology. This research refers to the Research and Development model which was developed using 7 research procedures, namely: research and data collection, planning, product draft development, initial field testing, product revision, field testing, and product revision. The results of this development research are: (1) producing Integrated Thematic PJOK teaching materials based on simple games on Theme 1 Rukun Life and learning videos (VCD) Integrated Thematic PJOK based on simple games, (2) Integrated Thematic PJOK teaching materials based on simple games has criteria validity with the results of the validation of the Integrated Thematic PJOK material reached 92%, the results of the validation of the teaching material design experts reached 93%, the results of the validation of learning experts reached 96%, the results of the validation of practitioners / teachers reached 94%, the results of student responses reached 97% and 94%. This shows that the teaching materials developed are suitable for use, beneficial for students, interesting and fun so that students are motivated and active in the Integrated Thematic PJOK learning process.